Observation on the Effect of Xiao Chaihu Tang Combined with Acupuncture on the Postoperative Nutritional Status of Lung Cancer Patients - Wang, Yan; Chen, Changle (Indian Journal of Pharmaceutical Education and Research, 2025)
Aim: Lung Carcinoma (LC) is still one of the malignant neoplastic diseases with the fastest-growing morbidity and mortality worldwide. This study observes the influence of traditional Chinese medicine acupuncture and moxibustion on nutritional status and Cancer-Related Fatigue (CRF) in post-surgical LC patients, thus providing new references for the future treatment of LC. Materials and Methods: 94 LC patients admitted from March 2021 to May 2023 were selected as the research participants for a randomized controlled trial, were divided into a control group (n=47) and an experimental group (n=47) for routine postoperative rehabilitation and Xiao chaihu Tang combined with acupuncture and moxibustion based on routine postoperative rehabilitation, respectively. Changes in CRF scores, T-lymphocyte subpopulations and cell counts before and after treatment were compared between the 2 groups and differences in nutrient proteins were detected. Results: CRF scores were all lower in the experimental group than in the control group after treatment (p<0.05). CD3+ and CD4+ decreased and CD8+ increased after treatment in the control group (p<0.05), but there was no significant change in the experimental group (p>0.05). In addition, White Blood Cells (WBC), Neutrophils (NEU) and Platelets (PLT) were higher in the experimental group than in the control group after treatment (p<0.05). Finally, it was seen that the after treatment nutritional status of the experimental group was more favorable than that of the control group. Conclusion: Xiao chaihu Tang combined with acupuncture and moxibustion exert a positive effect on alleviating CRF and improving nutritional status in post-surgical LC patients.
Keywords: Acupuncture and moxibustion; Cancer-related fatigue; Immune function; Lung; carcinoma; Nutritional Status; Xiao chaihu Tang